2012
DOI: 10.1136/heartasia-2011-010090
|View full text |Cite
|
Sign up to set email alerts
|

Dietary predictors of early-onset ischaemic heart disease in a sample drawn from a Pakistani population

Abstract: 50-73% of variance in IHD due to dietary pattern can be predicted with 91.8% accuracy within the study sample. The study lays ground for future research, as well as providing help in planning preventive dietary strategies to counter the escalating burden of IHD in Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
1
4
0
2
Order By: Relevance
“…Risiko bahaya kejadian gagal jantung berturut-turut yaitu 3,77, 4,64, 4,89, dan 7,39 kali pada 1000 orang per tahun untuk frekuensi asupan makanan yang digoreng dari <1 kali seminggu, 1-3 kali per minggu, 4-6 kali per minggu, dan >7 kali tiap minggunya 6 . Penelitian di Pakistan dengan metode case control menunjukkan bahwa pola makan yang tidak sehat (tinggi produk hewani, tinggi garam, snack asin, gorengan, ghee dan mentega serta rendah buah, sayuran dan ikan) secara signifikan berhubungan dengan risiko penyakit jantung iskemik 12 .…”
Section: Results (Hasil)unclassified
See 1 more Smart Citation
“…Risiko bahaya kejadian gagal jantung berturut-turut yaitu 3,77, 4,64, 4,89, dan 7,39 kali pada 1000 orang per tahun untuk frekuensi asupan makanan yang digoreng dari <1 kali seminggu, 1-3 kali per minggu, 4-6 kali per minggu, dan >7 kali tiap minggunya 6 . Penelitian di Pakistan dengan metode case control menunjukkan bahwa pola makan yang tidak sehat (tinggi produk hewani, tinggi garam, snack asin, gorengan, ghee dan mentega serta rendah buah, sayuran dan ikan) secara signifikan berhubungan dengan risiko penyakit jantung iskemik 12 .…”
Section: Results (Hasil)unclassified
“…Makanan yang digoreng tidak hanya berisiko meningkatkan terjadinya PJK. Penelitian di Pakistan pada tahun 2012 menunjukkan bahwa pola makan yang tidak sehat termasuk makanan yang digoreng secara signifikan memiliki hubungan dengan Penyakit Jantung Iskemik (PJI) 12 . Selain itu, studi cohort yang dilakukan tahun 2015 pada peserta Physicians' Health Study membuktikan bahwa semakin sering mengkonsumsi gorengan tiap minggunya, semakin tinggi pula risiko bahaya terjadinya gagal jantung 6 .…”
Section: Discussion (Pembahasan) Hubungan Pola Konsumsi Makanan Gorenunclassified
“…The findings of our study were different as in our study high levels of triglycerides and LDL were common among almost half of the CAD patients but for controls, only one-third of respondents had elevated levels of triglycerides and LDL. Rafique et al reported that in the population of Pakistan, diets with a high frequency of butter, ghee, eggs, and beef has been associated with an increased risk of CAD [ 25 ]. Our study reported similar findings as there was a significant association between CAD risk and chicken, beef, eggs, yogurt, and junk food intake, as well as eating fish less than twice per week.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reported similar findings as there was a significant association between CAD risk and chicken, beef, eggs, yogurt, and junk food intake, as well as eating fish less than twice per week. Findings of another study [ 25 ] revealed that fruit consumption had a protective effect against CAD. These findings are similar to the findings of our study which reported that fruit and vegetable consumption had a protective effect against CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation